2021
DOI: 10.3389/fmicb.2021.736484
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tick-Borne Pathogens and Genotyping of Coxiella burnetii in Rhipicephalus microplus in Yunnan Province, China

Abstract: Rhipicephalus microplus, a vector that can transmit many pathogens to humans and domestic animals, is widely distributed in Yunnan province, China. However, few reports on the prevalence of tick-borne pathogens (TBPs) in Rh. microplus in Yunnan are available. The aim of this study was to detect TBPs in Rh. microplus in Yunnan and to analyze the phylogenetic characterization of TBPs detected in these ticks. The adult Rh. microplus (n = 516) feeding on cattle were collected. The pooled DNA samples of these ticks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…In recent decades, much attention has been paid to Rickettsiales bacteria circulating in this area. Numerous studies have been performed and many bacterial species belonging to the order Rickettsiales have been characterized in Yunnan Province ( Liang et al, 2012 ; Liu et al, 2020 ; Jiao et al, 2021 ). One study revealed high positive rates of SFGR in domestic animals (goats, dogs, and cattle), and proved the existence of R. heilongjiangensis and a distinct Rickettsia ( Liang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, much attention has been paid to Rickettsiales bacteria circulating in this area. Numerous studies have been performed and many bacterial species belonging to the order Rickettsiales have been characterized in Yunnan Province ( Liang et al, 2012 ; Liu et al, 2020 ; Jiao et al, 2021 ). One study revealed high positive rates of SFGR in domestic animals (goats, dogs, and cattle), and proved the existence of R. heilongjiangensis and a distinct Rickettsia ( Liang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…R. jingxinensis in ticks from Yunnan Province ( Liu et al, 2020 ). In Jiao et al (2021) detected multiple tick-borne pathogens circulating in Rhipicephalus microplus ticks from Yunnan, including Ca. R. jingxinensis, A. marginale , and Coxiella burnetii .…”
Section: Introductionmentioning
confidence: 99%
“…C. burnetii can also be transmitted through aerosols to practitioners in slaughterhouses and meat processing plants. In addition, a variety of ticks can carry C. burnetii, which play a role in the transmission between animals (18,19). The patient had an epidemiological history of visiting a slaughterhouse to purchase fresh beef in our case.…”
Section: Discussionmentioning
confidence: 76%
“…The long or near full-length sequences of these phylogenetically important genes were obtained for the first time, and it was phylogenetically characterized as a species of the subgroup around R. japonica . Until now, it was only identified in East Asia, including Republic of Korea, and Southwestern and Northern China ( Guo et al., 2019 ; Qin et al., 2019 ; Kim et al., 2020 ; Li et al., 2020b ; Seo et al., 2020 ; Jiao et al., 2021b ; Park et al., 2021 ), whereas it was, for the first time, identified in Jiangsu province, Eastern China. Similar to other species (i.e., R. heilongjiangensis and R. japonica ) in this subgroup, Candidatus R. jingxinensis was observed to be able to infect humans with clinical characteristics of fever, erythematous rash, and eschar ( Kim et al., 2020 ), indicating a potential threat to public health of the area.…”
Section: Discussionmentioning
confidence: 99%